A method‐centric 'User Manual' for the mitigation of diffuse water pollution from agriculture. (June 2016) - Cuttle, S. P.; Newell‐Price, J. P.; Harris, D.; Chadwick, D. R.; Shepherd, M. A.; Anthony, S. G. A.; Macleod, C. J. A.; Haygarth, P. M.; Chambers, B. J.
Abstract: We describe the development of a manual of methods for mitigating diffuse water pollution from agriculture and its important influence on policy and practice in England and Wales. The objective of the 'User Manual' was to provide policy makers and those implementing policies with information about the cost, effectiveness and applicability of potential methods in a form that would be readily understood by non‐specialists. The 'User Manual' was based on earlier reports synthesizing available research data and, where data were unavailable, used expert elicitation. The outcome generated 44 potential methods (under the broad categories of land use, soil management, livestock management, fertilizer management, manure management and farm infrastructure) and described the simultaneous impact of applying each method on losses of nitrate, phosphorus and faecal indicator organisms relative to baseline losses. Estimates of cost and effectiveness were presented at the whole‐farm level for seven model farm types. Methods differed widely in their cost‐effectiveness and applicability to the different model farms. Advantages and limitations of the approach are discussed and subsequent developments of the original 'User Manual' are described, together with the opinions of catchment officers who have used the 'User Manual' to implement mitigation methods on farms.